Safety Methods for Mitigating Thermal Runaway of Lithium-Ion Batteries—A Review - Jun Deng; Zhen Hu; Jian Chen; Jingyu Zhao; Zujin Bai (Fire, 2025)
Lithium-ion batteries (LIBs) are widely used as energy storage units in electric vehicles, mobile phones, and other electric devices due to their high voltage, large capacity, and long cycle life. Lithium-ion batteries are prone to thermal runway (TR), resulting in fires and explosions, which can seriously hinder the commercial development of LIBs. A series of safety methods has been studied to prevent TR of LIBs. The safety methods for suppressing TR in LIBs were reviewed, including safety equipment method, material modification method, thermal management method, and cooling method. The mechanism, advantages and disadvantages, and future applications of the TR suppression method are discussed. The effectiveness of the proposed safety method was evaluated through technical analysis and experimental testing, and the inhibitory effects of different safety methods on battery TR were summarized. The future trend of suppressing TR is discussed by summarizing and generalizing existing technologies for suppressing thermal runaway. This study provides a reference for exploring more effective methods to mitigate TR in the future.